SOSIALISASI PENTINGNYA PERJANJIAN SPONSORSHIP ANTARA PERTUNI PROVINSI BALI DENGAN PIHAK SPONSOR - Puspadewi, Anak Agung Ayu Intan; Prawitasari, Putu Putri; Dewi, Ni Ketut Ari Kesuma (Jurnal Abdi Insani, 2024)
PERTUNI Bali often organizes annual activities that generally require funding. To ensure the smooth running of these activities and to obtain the necessary funds, they usually use sponsorship. Sponsorship is a form of support provided by individuals, companies, or organizations to an event or project in exchange for certain benefits. This sponsorship is typically conducted verbally between PERTUNI and the sponsor, but often sponsors do not provide according to the agreement. Therefore, having a written agreement is crucial to bind both parties. The purpose of this service is to educate PERTUNI members on the importance of written agreements, especially when collaborating with sponsors. It aims to provide an understanding of creating agreements with sponsors through mutual consent. The method used in this service involves conducting socialization through presentations to PERTUNI members. The presentation covers materials related to sponsorship agreements and their importance. The stages of the process include surveying PERTUNI, data collection, interviews, drafting, socialization, and evaluation. The outcome of the service shows that sponsorship is a form of support that can be in the form of money, products, services, or other resources. After discussions with PERTUNI members, it was found that some members still do not understand sponsorship agreements. This socialization explained that written agreements are crucial when collaborating with sponsors, as they formalize the agreement, outline the rights and obligations of both parties, and bind them. Following the presentation, methods for drafting sponsorship agreements based on mutual consent were discussed, which will bind both parties. In conclusion, sponsorship refers to the support provided by sponsors to the organizers. Sponsorship activities should ideally be conducted using written agreements.